A finite element study of rain intensity on skid resistance for permeable asphalt concrete mixes. (30th September 2019) - Tang, Tianchi; Anupam, Kumar; Kasbergen, Cor; Scarpas, Athanasios; Erkens, Sandra
Graphical abstract: Highlights: CT-scanned meshes of AC mixes representing realistic inner structures of the mix. FE based framework to analyze the role of various rainfall intensities on wet skid resistance. Parametric analysis to study the effect of various parameters on wet skid resistance-rainfall intensity relationship. Validation of the proposed FE model against field test data and previous empirical models. Abstract: Safe highway operations are one of the major concerns of pavement engineers and authorities. The reduction of skid resistance during rainy weather poses high risk for safe driving. Wet skid resistance varies under different rainfall intensities and is influenced by many factors such as permeability of asphalt material, pavement geometric design, and tire operating conditions. Empirical studies could offer useful understanding of mechanisms of wet skid resistance and its influencing factors, however, the applicability of the empirical relationships are restricted as soon as there is a change in one of the relevant factors. In recent years, the advancement of the finite element tools has enabled researchers to simulate the tire-fluid-pavement interaction in a more realistic way. However, to the best of the authors' knowledge, the current available numerical models either do not include the real microstructures of the pavement or ignore the water infiltration through the pavement voids in the simulations. Therefore, this paper aims to providing a numerical tool to evaluate the wet skid resistance at various rainfall intensity conditions considering the effects of pavement geometric design, tire tread design and tire operating conditions. The surface characteristics and porous microstructures of the pavement are included in the model in a way that both the vertical water flow into the asphalt concrete and surface flow on the pavement can be captured in the simulation. The effects of several pronouncing influential factors as mentioned above are quantified. Such a model upon validation is expected to provide an easy and reliable tool for pavement engineers to evaluate wet skid resistance under rainy weather more accurately which can be incorporated into pavement management systems for safety highway operation.